Fun & games for workplace learning - Leigh, Elyssebeth; Kinder, Jeff. (Sydney : McGraw-Hill, 2001)
A compilation of 40 original Australian designs relevant to current workplace learning needs both here and internationally. The book is easy to understand and provides information on how to use the exercises as well as guiding the reader through selecting, running and debriefing to achieve learning outcomes.
Part One. Learning about Simulations and Games : Welcome to Kalfira! -- Part Two. Games for Workplace Learning: 1. Where do I sit?; 2. Everyday in every way we're becoming a better team; 3. The team needs you; 4. Where's my suit?; 5. The human email; 6. Bushfire values; 7. A values game; 8. The body mirror; 9. The me tree; 10. Thumbs up, thumbs down; 11. Reasonable force; 12. The big picture; 13. (You can) change the world; 14. Listen to us; 15. The listening stakes; 16. The work grid; 17. Build-a-bridge; 18. Half of ten is ...?; 19. Group resume; 20. Let's work together; 21. Stream of revision; 22. Lucky dip revision; 23. Outrageous statements; 24. Lux Luther: raiders of the lost consequences; 25. Through a glass, darkly; 26. Yesterday, today, tomorrow; 27. Creating a farrago; 28. Top team; 29. The question of ethics; 30. Model manager; 31. Larry Liftright; 32. Almost inifite equations; 33. Hepatitis C game; 34. Hidden message; 35. Burgeon Bridge; 36. Puzzling culture; 37. Win win; 38. Customer connections; 39. Bell Communications; 40. Introducing evaluation.
"Comes complete with CD containing diagrams, charts, templates and other ancillary material which can easly be used for overheads and/or data projection" --Back cover.
System requirements not available.
"40 structured learning activities to enhance workplace learning programs" --T.p. and cover.
Bibliography: p. 233-234.
mizan
Keywords: Educational games; Education -- Simulation methods